2022
DOI: 10.3390/jcm11030805
|View full text |Cite
|
Sign up to set email alerts
|

Low miR 511-5p Expression as a Potential Predictor of a Poor Nutritional Status in Head and Neck Cancer Patients Subjected to Intensity-Modulated Radiation Therapy

Abstract: Nutritional deficiencies, including malnutrition and its irreversible type cachexia, are often observed in patients with head and neck cancer (HNC). Among the various factors contributing to the occurrence of these disorders, inflammation seems to be crucial. The potential regulatory properties of miR-511-3p, e.g., post-translational alteration of expression of genes with protein products that are involved in inflammation, may be related to nutritional deficiencies observed in HNC patients. Therefore, the aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Approximately half of the patients' prealbumin and albumin levels decreased below normal. Therefore, the mean Studies have shown that acute or chronic inflammation of different degrees is closely related to the occurrence of malnutrition, and in diseases or injuries, metabolic and dietary intake changes occur [14,39,40]. There is a close interaction between inflammation and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately half of the patients' prealbumin and albumin levels decreased below normal. Therefore, the mean Studies have shown that acute or chronic inflammation of different degrees is closely related to the occurrence of malnutrition, and in diseases or injuries, metabolic and dietary intake changes occur [14,39,40]. There is a close interaction between inflammation and malnutrition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the aforementioned, Mazurek et al . (2022), outlined in their elegant paper [ 45 ], that, MiR-511-3p plays an important role in inflammation via the regulation of peroxisome proliferator-activated receptor γ (PPARγ) expression and Toll-like receptor 4 (TLR4) regulation in human dendritic cells (DCs). PPARγ is known to regulate many DC functions including pro-inflammatory cytokine production, migration, antigen presentation and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that acute or chronic in ammation of different degrees is closely related to the occurrence of malnutrition, and in diseases or injuries, metabolic and dietary intake changes occur. [15,40,41] There is a close interaction between in ammation and malnutrition. The existence of in ammation contributes to the development of malnutrition and limits the effectiveness of nutritional interventions.…”
Section: Clinical E Cacy Analysismentioning
confidence: 99%